the philosophy of liberation for/with children: in search of liberation and the creation of an ageless pueblo - padilla rosas, erick javier (childhood & philosophy, 2024)
From its origins, the philosophy of liberation has had both a critical and a creative aspect. The first seeks to critically examine domination, dependency, and the permanent effects of colonization. The second aims to create and re-create the liberation of peoples, developing and reconstituting ways of existing, imagining, thinking, and philosophizing that surpass colonial ways of existing, imagining, thinking, and philosophizing. Thus, for the philosophy of liberation, the liberation of peoples is distinguished from the notions of emancipation and freedom that hide reality under processes of ideologization. An example of the latter is modernity’s notion of emancipation. In this paper, I propose to approach the critical and creative function of the philosophy of liberation from a childist lens in which not only the voices of children are considered, but also the adultist and modern vision of emancipation is overcome. This will be particularly important to continue the legacy of the philosophy of liberation, and its mission to criticize and create from the political and philosophical participation of the victims in the processes of ideologization. From this legacy the children are participants, who, by engaging in pedagogical practices of liberation, act as un pueblo, a collective political actor without age. of the latter is modernity’s notion of emancipation. In this paper, I propose to approach the critical and creative function of the philosophy of liberation from a childist lens in which not only the voices of children are considered, but also the adultist and modern vision of emancipation is overcome. This will be particularly important to continue the legacy of the philosophy of liberation, and its mission to criticize and create from the political and philosophical participation of the victims of the processes of ideologization. Of this legacy, the children are participants, who, by engaging in pedagogical practices of liberation, act as un pueblo, a collective political actor without age.